Human papillomavirus and the risk of Barrett's esophagus. Issue 5 (14th August 2012) - El‐Serag, H. B.; Hollier, J. M.; Gravitt, P.; Alsarraj, A.; Younes, M.
Summary Human papillomavirus (HPV) is strongly associated with squamous esophageal cancer. The potential role of HPV in Barrett's esophagus (BE) has been examined but remains unclear. The aim of the study was to determine the prevalence of HPV in esophageal and gastric tissues obtained from patients with and without BE. We designed a cross‐sectional study was conducted with prospective enrollment of eligible patients scheduled for esophagogastroduodenoscopy (EGD). All participants had biopsies of endoscopic BE, squamous‐lined esophagus, and stomach. Immunohistochemistry (IHC) on formalin‐fixed and paraffin‐embedded tissue was conducted using monoclonal antibodies. Polymerase chain reaction (PCR) for HPV was performed on DNA extracted from esophageal biopsies snapped frozen within 30 minutes after endoscopic capture. The Roche HPV Linear Array Assay with PGMY primers that has high sensitivity for detecting 37 types of HPV was used. A total of 127 subjects were included: 39 with definitive BE had IHC done on samples from non‐dysplastic BE, squamous esophagus, gastric cardia, and gastric body; and 88 control patients without BE had IHC done on squamous esophageal samples, gastric cardia, and gastric body. HPV was not detected in any of the samples in either group. For confirmation, HPV DNA PCR was performed on randomly selected samples from 66 patients (both esophagus and BE from 13 patients with BE, and 53 esophagus from patients without BE); no sample had HPV DNA detected via PCR in the presence of adequate quality control. HPV infection does not play a role in the formation of non‐dysplastic Barrett's esophagus in men in the United States.